Crumpled structures as robust disordered mechanical metamaterials - Gerard Giménez-Ribes; Melika Motaghian; Erik van der Linden; Mehdi Habibi (Materials & Design, 2023)
Mechanical metamaterials such as origami or ordered 3D printed structures have shown tremendous applications in science and technology. However, the main disadvantage of these systems is their dependency on a perfectly ordered structure, making them sensitive to defects. Disordered metamaterials offer a way to circumvent this sensitivity. Within disordered metamaterials, crumpled systems have recently received increased attention due to their intriguing properties such as negative Poisson’s ratio, low density, high mechanical shock absorption, and easy manufacturing process. Mechanical relaxation of these systems was successfully explained by stretched exponential and logarithmic models, typically used for complex relaxation in amorphous systems. This drove researchers to study crumpled systems as amorphous systems with a complex energy landscape. Further research remarked similarities between crumpled structures and other metastable systems such as glasses, by studying the mechanical memory effect. Edward’s statistical mechanics was also applied to crumpled systems to unravel their statistical properties. In this review, we summarize different aspects of crumpled materials and their potential to be exploited for designing new robust disordered metamaterials. Finally, we build on the current knowledge and introduce a design principle to make crumpled origami-like structures with robust mechanical responses.